Neolithic agricultural management in the Eastern Mediterranean: new insight from a multi-isotope approach - Vaiglova, P (2016)
The work presented in this dissertation explores the nature of agro-pastoral strategies developed by Neolithic farmers as a way to understand how early food production was inter-twined with environmental and socio-economic opportunities and constraints. Towards this end, a multi-isotope approach is used to address questions of scale and intensity of crop cultivation and animal management at the archaeological sites of Kouphovouno, southern Greece, Makriyalos, northern Greece, and Çatalhöyük, south-central Turkey. Measurements of stable carbon, nitrogen, oxygen and strontium isotope values of carbonized plant remains, human and animal bone collagen and animal tooth enamel are used to examine the similarities and differences in the types of treatments that individual species of plants and animals received during the agricultural cycle at the distinct locations. The results show that farmers at the three sites developed variable methods for exploiting the arable and pastoral landscape and catering to their economic and culinary needs. The discussion considers the implications of these findings to our understanding of the complexity and adaptability of early farming systems.